Anti-malarial activity of extract of sponge (Aaptos sp) from Tanjung Pecaron, Indonesia - Mohd. Noor, Noriah; Abdillah, Syamsudin; Nurhayati, Awik Puji Diah (2012)
Malaria has been a major health problem in tropical countries. Various malaria eradication efforts have been carried out but the prevalence of malaria is still high. Hence, the need for alternative drug is acute. This study aims at investigating the in vivo antimalarial activity of extracts of sponge (Aaptos sp) taken from Tanjung Pecaron, Indonesia. The safety of the extract was also investigated in ICR mice by the acute oral toxicity test. The crude ethanol extract of Aaptos sp (20, 80, 320 and 1280 mg/kg) was investigated for its antimalarial activity against P> berghei during early infection, established infection and residual/prophylactic activity. The acute toxicity of the extract were also investigated. The extract of Aaptos sp demonstrated significant (p<0.05) schizonticidal activity in all the three antimalarial evaluation models. The acute toxicity test showed that the extract of Aaptos sp is toxicologically safe by oral administration. The extract of sponge (Aaptos sp) has anti-malarial activity in vivo.